Carbon nanotubes with conductance-preserving covalent functionalities - Liu, Chao (2014)
Single walled carbon nanotubes (SWCNTs) have attracted enormous attention due to their exceptional electrical properties. The full potential of SWCNTs, however, has not been harnessed due to several major challenges. One of them is insolubility of SWCNTs, which causes a poor processability for fabricating SWCNT-based devices. This problem has been alleviated with the covalent attachment of chemical functionalities to SWCNTs. Covalent chemical functionalizations have been proven capable of tailoring the interactions of nanotubes with surrounding environments, improving the solubility and allowing much easier manipulation and processing of such a discrete material. Unfortunately, covalent functionalizations reported so far are all associated with significant degradation in the electrical conductance of SWCNTs, due to the sp2 _ sp3 rehybridization of the sidewall carbon atoms anchoring the functional groups. Recently, carbene has been predicted by several theorists as a suitable covalent functional group that can modify SWCNT sidewalls without degrading the electrical conductance. In this thesis, the effects of dichlorocarbene functional groups on the electrical properties of SWCNTs were carefully examined. The electrical conductance of an m-SWCNT was firstly measured in the configuration of back-gated field effect transistor (FET). The conductance-sustaining effect of dichlorocarbene was clearly confirmed through an in-situ comparison between similar degrees of dichlorocarbene functionalization (only 13 ~ 23% drop in the conductance) and hydrogenation (more than 75% drop) on the same m-SWCNT. In this comparison experiment, conductive-AFM was employed to measure the linear resistance of the m-SWCNT, and X-ray Photoelectron Spectroscopy was used to quantify the degrees of both functionalizations. The effects of dichlorocarbene functional groups on the electrical properties of s-SWCNTs were also examined. The electrical conductance of the functionalized s-SWCNT dropped more than 1 order of magnitude, in sharp contrast to the functionalized m-SWCNTs. The selectivity of dichlorocarbene in suppressing the conductance of s-SWCNTs was further confirmed through measurements on 12 network SWCNT devices with on/off ratios ranging from 3 to 103. Apart from the significant conductance degradation, both Raman scattering and electrical measurements suggested that the gate dependence of the s-SWCNT conductance was lost upon dichlorocarbene functionalization. A control experiment in conjugation with the Electrostatic Force Microscopic (EFM) measurements suggested that such s- to m-SWCNT conversion is due to structural changes inside s-SWCNTs rather than in the nanotube/electrode contacts. All the chemically induced changes in SWCNTs were able to recover upon thermal annealing at 450°C in ambient condition for 1 hour, indicating dichlorocarbene covalent functionalization to be a reversible process.